On the use of a chirped Bragg grating as a cavity mirror of a picosecond Nd : YAG laser. (1st March 2016) - Zubko, A E; Shashkov, E V; Smirnov, A V; Vorob'ev, N S; Smirnov, V I
Abstract: The first experimental evidence is presented that the use of a chirped volume Bragg grating (CVBG) as a cavity mirror of a Q-switched picosecond Nd : YAG laser with self-mode-locking leads to significant changes in the temporal parameters of the laser output. Measurements have been performed at two positions of the CVBG: with the grating placed so that shorter wavelengths reflected from its front part lead longer wavelengths or with the grating rotated through 180°, so that longer wavelengths are reflected first. In the former case, the duration of individual pulses in a train increased from ∼35 to ∼300 ps, whereas the pulse train shape and duration remained the same as in the case of a conventional laser with a mirror cavity. In the latter case, the full width at half maximum of pulse trains increased from ∼70 ns (Nd : YAG laser with a mirror cavity) to ∼1 ms, and the duration of individual pulses increased from 35 ps to ∼1.2 ns, respectively, which is more typical of free-running laser operation.